Occurrence and molecular genotyping of Giardia duodenalis and Cryptosporidium spp. in wild mesocarnivores in Spain - Mateo, Marta; Hernández de Mingo, Marta; Lucio, Aida de; Morales, Lucía; Balseiro, Ana; Espí, Alberto; Barral, Marta; Lima-Barbero, José Francisco; Habela, Miguel Ángel; Fernández-García, José L.; Calero Bernal, Rafael; Köster, Pamela C.; et al. (Veterinary Parasitology, 2017)
There is a surprisingly scarce amount of epidemiological and molecular data on the prevalence, frequency, and diversity of the intestinal protozoan parasites Giardia duodenalis and Cryptosporidium spp. in wildlife in general and mesocarnivore species in particular. Consequently, the extent of the cyst/oocyst environmental contamination attributable to these wild host species and their potential implications for public veterinary health remain largely unknown. In this molecular epidemiological survey a total of 193 individual faecal samples from badgers (Meles meles, n = 70), ferrets (Mustela putorius furo, n = 2), genets (Genetta genetta, n = 6), Iberian lynxes (Lynx pardinus, n = 6), beech martens (Martes foina, n = 8), mongooses (Herpestes ichneumon, n = 2), otters (Lutra lutra, n = 2), polecats (Mustela putorius, n = 2), red foxes (Vulpes vulpes, n = 87), wildcats (Felis silvestris, n = 2), and wolves (Canis lupus, n = 6) were obtained from road-killed, hunted, and accidentally found carcasses, and from camera-trap surveys or animals entering rescue shelters, during the period December 2003–April 2016. Investigated specimens were collected in five Spanish autonomous regions including Andalusia (n = 1), Asturias (n = 69), Basque Country (n = 49), Castile-La Mancha (n = 38), and Extremadura (n = 36). The presence of cysts/oocysts was confirmed by PCR-based methods targeting the small subunit (ssu) ribosomal RNA gene of these parasite species. Genotyping of the obtained isolates were attempted at appropriate markers including the glutamate dehydrogenase (G. duodenalis) and the 60-kDa glycoprotein (C. parvum and C. ubiquitum) loci. Overall, G. duodenalis was detected in 8% (7/87) of red foxes, a single beech marten, and a single wolf, respectively. Cryptosporidium was identified in 3% (2/70) of badgers, 8% (7/87) of red foxes, a single genet, and a single mongoose, respectively. None of the nine G. duodenalis isolates generated could be genotyped at the assemblage/sub-assemblage level. Out of the nine ...